The theoretical and experimental investigation of temperature and salinity gradients in salt gradient solar ponds [Tuz Tabakali Güneş Havuzlarinda Sicaklik ve Yoǧunluk Gradyenleri̇ni̇n Teori̇k ve Deneysel Olarak İncelenmesi̇] - (:unkn) unknown (My University, 2005)
In this study, both experimental and theoretical investigations were carried out in order to determine whether sodium carbonate salt which has not been used up to now for establishing salinity gradients is suitable for establishing salinity gradient in Salt Gradient Solar Pond (SGSP) or not. The heat storage ability of a solar pond was also examined. For this purpose, a small scale pond in the laboratory conditions was constructed for the experimental work and also one dimensional mathematical model for the SGSP's heat and mass transfer was developed. Differential equations obtained through by the developed model were solved numerically using finite difference method. The experimentally and theoretically obtained results showed that in order to establish temperature gradient in the sodium carbonate solution pond, a salinity gradient with salinity of about 12 % needs established.
Keywords: Mathematical model; Salt gradient solar pond; Sodium carbonate